Amino Acid Profile Analysis of Paramphistomum Species - Gupta, Sheela (Journal for Research in Applied Sciences and Biotechnology, 2022)
This study investigates the amino acid profiles of various species of Paramphistomum, a group of parasitic flatworms known to affect livestock. By analyzing the amino acid composition, we aim to better understand the nutritional and metabolic needs of these parasites. Our findings reveal distinct amino acid profiles across different Paramphistomum species, which could have implications for developing targeted treatments and control measures. This research provides valuable insights into the biochemical characteristics of these parasites and underscores the importance of amino acid profiling in parasitology.